THE EFFECT OF FINGER HOLD RELAXATION ON POST OPERATING PAIN IN PATIENTS AT RSUD DR. RASIDIN PADANG - Fridalni, Nova -; Yanti, Etri (Jurnal Kesehatan Saintika Meditory, 2023)
Everyone can experience pain to different degrees. Causes of pain include the result of trauma or surgery. Pain after surgery usually makes the patient feel very sick. The average patient feels severe pain in the first 2 hours postoperatively. The finger grip is very simple technique. This technique will produce impulses that are sent through non-nociceptor afferent nerve fibers which result in the "gate" being closed so that the pain stimulus is inhibited and reduced. This study aims to determine the effect of hand-held relaxation techniques on the pain scale of postoperative patients in the surgical inpatient room of Dr. Rasidin Padang. This research is a quasi-experimental research with one group pre-posttest approach. The study population was all postoperative patients who were treated in the operating room of RSUD dr. Rasidin Padang who experienced pain and the number of samples in this study were 16 respondents who were taken by purposive sampling technique. Analysis of research data using paired t-test. The results showed that the mean respondent's pain scale before the intervention was 4.875 with a minimum pain scale of 4 and a maximum of 6 and the mean post-intervention pain scale was 4.25 with a minimum pain scale of 3 and a maximum of 4. There were differences in the mean respondent's pain scale before and after the intervention with p-Value  = 0.003.